Teaching Low Brass - Maxwell, Steven (Open textbook library., 2018)
The purpose of this textbook is to provide resources about teaching low brass instruments to music educators and future music educators. The book was developed by the author as part of the open/alternative textbook initiative at Kansas State University. It Is the textbook used for the Kansas State University course Music 239-Low Brass Techniques and Materials. The textbook focuses on two areas: basic information including pedagogical material for teaching low brass students and low brass etudes. The information is divided into several categories including brass history, the overtone series, general intonation tendencies, embouchure, instruments and equipment, literature, maintenance, vibrato, and low brass in the marching band. Pedagogical material is interspersed throughout each of the chapters. Etudes are incorporated in the appendix of the textbook. These etudes are intended to be used in a laboratory setting with future music educators learning each low brass instrument for the first time. Instrument fingerings, slide positions, and simple warm-up material is also available in the appendix.